Praktik Utang Piutang yang Dibayar dari Hasil Panen Padi pada Masyarakat Nagari Tabek Sirah Kabupaten Pasaman Barat Perspektif Fikih Muamalah - Gina Isyania; Busyro Busyro (Lembaga Yasin AlSys, 2026)
The lending and borrowing practices between toke (middlemen) and rice farmers in Nagari Tabek Sirah, Pasaman Barat Regency, have from the outset required an additional payment at the time of loan settlement, which is made through the rice harvest. This additional payment is not explicitly stated as interest but is implied through the setting of a paddy price lower than the market price, thereby raising concerns about elements that may potentially conflict with sharia principles. This study aims to comprehensively examine the loan practices repaid from rice harvests in Nagari Tabek Sirah and to analyze their conformity with the provisions of fiqh muamalah, particularly regarding the qardh contract and the prohibition of riba. The research employs a qualitative method with a fieldwork approach through interviews and direct observation. Primary data sources consist of farmers and toke, while secondary data sources include community members familiar with the lending practices, as well as books, journals, and articles. Data were analyzed descriptively through stages of data collection, classification, and interpretation of findings based on the fiqh muamalah framework. The results show that the lending and borrowing practices repaid from rice harvests arise from the community’s economic conditions, which are highly dependent on rice farming that is harvested only once a year, prompting them to meet their living needs by borrowing from toke. Formally, this practice satisfies the pillars and conditions of a qardh contract according to fiqh muamalah. However, the repayment mechanism that, from the outset, requires an additional payment through the setting of a paddy price below the market price renders this practice inconsistent with the basic principle of qardh, which should be free from riba. These findings affirm that the lending and borrowing practice deviates from the provisions of Islamic law and indicate the need to strengthen muamalah literacy and to reform agricultural financing patterns so that they are fairer and more sharia-compliant for farmers.